Biased Knowers, Biased Reasons, and Biased Philosophers - Veber, Michael (International journal for the study of skepticism, 2024)
In Bias: A Philosophical Study, Thomas Kelly offers a response to epistemological skepticism grounded in his account of bias. According to Kelly, the classic argument for skepticism is best understood as an attempt to show that our commonsense beliefs are biased against the skeptic. Kelly grants that this is true but argues that biased beliefs can still be knowledge. I offer two objections. First, if we are applying Kelly’s theory of bias to skepticism, it is best to think of the skeptic’s challenge to be that our anti-skeptical beliefs are based on what we know to be biased reasons. Kelly has not shown that this sort of bias is compatible with knowledge. Second, Kelly’s approach to the problem of skepticism is an example of what I have called “unambitious epistemology.” And, for that reason, it is not a satisfactory answer to skepticism.